Pengaruh Blended Learning Dan Gaya Belajar Terhadap Hasil Belajar IPA - Helen Purwatiningsih (JTP - Jurnal Teknologi Pendidikan, 2014)
This research aims to reveal the effect of instructional approaches and interper- sonal intelligency outcomes of integrated science. The experimental group used quantum learning approach by utilizing the educational, while the control group used ekspositori. The result of the study ANAVA and followed by Tukey’s test.The results indicate: (1) science learning outcomes of students who are learning to instructional quantum learning higher than expository; (2) there is an interaction effect between learning and interpersonal intel- ligence approach; (3) science learning outcomes of students who studied with quantum learning is higher than expository learning for groups of students with high interpersonal intelligence; (4) science learning outcomes of students who learned with expository instruk- tional is higher than the quantum learning for groups of students with low interpersonal intelligence.